Isolation and SAR studies of bicyclic iminosugars from Castanospermum australe as glycosidase inhibitors. - Kato, A; Hirokami, Y; Kinami, K; Tsuji, Y; Miyawaki, S; Adachi, I; Hollinshead, J; Nash, R; Kiappes, J; Zitzmann, N; Cha, J; Molyneux, R; et al. (Elsevier, 2015)
We report the isolation and structural determination of fourteen iminosugars, containing five pyrrolizidines and five indolizidines, from Castanospermum australe. The structure of a new alkaloid was elucidated by spectroscopic methods as 6,8-diepi-castanospermine (13). Our side-by-side comparison between bicyclic and corresponding monocyclic iminosugars revealed that inhibition potency and spectrum against each enzyme are clearly changed by their core structures. Castanospermine (10) and 1-deoxynojirimycin (DNJ) have a common d-gluco configuration, and they showed the expected similar inhibition potency and spectrum. In sharp contrast, 6-epi-castanospermine (12) and 1-deoxymannojirimycin (manno-DNJ) both have the d-manno configuration but the α-mannosidase inhibition of 6-epi-castanospermine (12) was much better than that of manno-DNJ. 6,8-Diepi-castanospermine (13) could be regarded as a bicyclic derivative of talo-DNJ, but it showed a complete loss of α-galactosidase A inhibition. This behavior against α-galactosidase A is similar to that observed for 1-epi-australine (6) and altro-DMDP.